2013
DOI: 10.1038/ncomms3742
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evolution of an alternating uni- and multicellular life cycle in Chlamydomonas reinhardtii

Abstract: The transition to multicellularity enabled the evolution of large, complex organisms, but early steps in this transition remain poorly understood. Here we show that multicellular complexity, including development from a single cell, can evolve rapidly in a unicellular organism that has never had a multicellular ancestor. We subject the alga Chlamydomonas reinhardtii to conditions that favour multicellularity, resulting in the evolution of a multicellular life cycle in which clusters reproduce via motile unicel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
177
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(186 citation statements)
references
References 38 publications
7
177
2
Order By: Relevance
“…Under selection for an increased rate of settling out of liquid suspension, one population evolved multicellular structures held together by an extracellular matrix (Ratcliff et al 2013), similar to those observed in isolate B2-01 in the present experiment (Fig. 2C).…”
Section: Defense Against Predationsupporting
confidence: 74%
See 1 more Smart Citation
“…Under selection for an increased rate of settling out of liquid suspension, one population evolved multicellular structures held together by an extracellular matrix (Ratcliff et al 2013), similar to those observed in isolate B2-01 in the present experiment (Fig. 2C).…”
Section: Defense Against Predationsupporting
confidence: 74%
“…Even in the amorphous clusters observed in isolate B2-01 and those that evolved in response to selection for setting rate (Ratcliff et al 2013), development is primarily clonal. Aggregation, through the incidental assimilation of free-swimming cells, was .…”
Section: Defense Against Predationmentioning
confidence: 99%
“…This basal positioning can be interpreted to mean that Gonium-like colony organization evolved successfully just once, and the more complex volvocine genera arose just once from among the Goniaceae (Herron and Michod 2008;Hayama et al 2010). The apparent difficulty of the transition between unicellular Chlamydomonas and colonial Gonium appears to contradict findings of experimental evolution in which unicellular yeasts and Chlamydomonas could be converted to facultative colonial forms in a short number of generations by artificial selection (Ratcliff et al 2012(Ratcliff et al , 2013. However, this discrepancy is not so paradoxical considering the degree of evolved functionality that arose in Gonium that distinguishes it from the disorganized cell aggregates produced during experimental evolution.…”
Section: Multicellular Innovations In the Volvocine Lineage Are Modifcontrasting
confidence: 46%
“…Cells in these palmelloid clusters had a significant reduction in growth rate and a significant increase in predator survivorship, suggesting a trade-off between survival and reproduction when cells are in a palmelloid cluster. Ratcliff et al (2013) experimentally evolved obligate multicellular Chlamydomonas clusters using centrifugation to select on cluster size. Evolved multicellular Chlamydomonas clusters contained over 100 cells descended from a single cell.…”
Section: Chlamydomonasmentioning
confidence: 99%
“…Evolved multicellular Chlamydomonas clusters contained over 100 cells descended from a single cell. Clusters were held together through secretion of an extracellular matrix (Ratcliff et al 2013). Sathe and Durand (2015) used a Euglenoid predator (Peranema trichophorum) to demonstrate Chlamydomonas can aggregate (in contrast to forming clusters through daughter cells failing to leave the mother wall) in clusters of 10-100,000 cells.…”
Section: Chlamydomonasmentioning
confidence: 99%